INCAS / Muhammad Iman Zulhakim Saat and Norarifah Ali - Saat, Muhammad Iman Zulhakim; Ali, Norarifah (Faculty of Art and Design, 2021)
Everyone will use a vehicle to go somewhere there want to be. They are susceptible to infection outside, for example when they enter a vehicle infected with the virus, which can infect others in the vehicle too. It can be spread through coughing, breath and touching. The design objective is to create a car product related to the new norm. Many problems and difficulties can be detected early in the research and at the same time creating new knowledge. These difficulties are in knowing what product can prevent covid-19 in vehicles. The coronavirus can live for hours to days on surfaces like countertops and doorknobs. How long it survives depends on the material the surface is made from. After research, we found a solution to prevent covid-19 infection in vehicles. The solution that was found is to create a car sanitizer. The function of car sanitizer is to sanitize inside the vehicle to prevent covid-19 in the vehicle. This product spray sanitizer to all parts inside the vehicle to remove viruses and this product has a usb port for other uses.